Pengaruh Supervisi Akademik Kepala Sekolah Dan Kompetensi Paedagogik Terhadap Kinerja Guru: Studi Kasus di SMA Swasta Sub Rayon 11 Parung Kabupaten Bogor - Parhan; EE. Junaedi Sastradiharja (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2018)
This study aims to find the influence between the principal academic supervision and paedagogic competence on the performance of private high school teachers Sub Rayon 11 Parung Bogor Regency. In this study the authors have found the theories to gain a deeper understanding of the definitions and concepts related to the concept of principal academic supervision, the concept of paedagogic competence and the concept of teacher performance. In this research the researcher use survey method, with correlation technique and simple and multiple regression analysis. Sampling was used by using the sample saturated, with the number of respondents 104 respondents at private SMA Sub Rayon 11 Parung Bogor regency. Data collection techniques used questionnaires, tests, observations, documentation and interviews. Data analysis techniques used descriptive analysis model, correlation coefficient, simple and multiple regression analysis. The results of this study show that First; there is a positive and significant influence of the principal's supervision on the performance of private high school teachers Sub Rayon 11 Parung Bogor Regency, this can be seen from the correlation coefficient of 0.649% at 99% confidence level (α = 0.01), while the magnitude of the influence or coefficient of determination R -square of 0.422 which means academic supervision of principal can give effect of teacher performance equal to 42,2% and the rest 57,8% influenced by other factor. For the direction of influence or regression coefficient obtained Ŷ = 18.508 + 0.823 X1 which means that each increase of one unit of academic supervision principal score affects the increase in teacher performance score of 0.823. Second; there is a positive and significant influence of teacher paedagogic competence on the performance of private SMA Sub Rayon 11 Parung Bogor Regency, this can be seen from the correlation coefficient of 0.706% at 99% confidence level (α = 0.01), while the magnitude of the influence or coefficient of determination R-square equal to 0.499 which means paedagogic competence give influence teacher performance equal to 49,9% and rest 50,1% influenced by other factor. For the direction of influence or regression coefficients diproleh Ŷ = 31.858 + 0.782 X2 which means that each increase of one unit of paedagogic competence score affects the increase in teacher performance score of 0.782. Third; there is a positive and significant impact of school principal supervision and paedagogic competence simultaneously on the performance of private high school teachers Sub Rayon 11 Parung Bogor Regency, this can be seen from the principal academic supervision and paedagogik competencies simultaneously on the performance of teachers 13.58% and the remaining 86.2% is determined by other factors. The direction of influence of the regression equation Ŷ = 0.636 X1 + 0.722 X2, which means that each increase in one unit of the principal's academic supervision score and paedagogic competence simultaneously affect an increase in the teacher performance score of 1.358.